Real-world experience of eltrombopag in immune thrombocytopenia - Mishra, Kundan (Am J Blood Res, 2020)
Immune thrombocytopenia (ITP) is characterized by decreased platelet count in the peripheral circulation. The first-line therapy is corticosteroids with 53-80% overall response rate. Eltrombopag has been used as second-line therapy in ITP for over a decade now. The long-term efficacy and safety profile have been widely reported in the western world. However, the data from the resource-constraint settings of the developing world is scarce. We aim to present the real-life experience of efficacy and safety of eltrombopag from the resource-constraint settings. This was a retrospective, single-center study conducted at a tertiary care hospital in Northern India from 2012-2019. On audit of medical records, patients of ITP receiving eltrombopag were screened for inclusion. Patients whose treatment outcomes were not available were excluded. Finally, 53 patients were analyzed using statistical packages of Python v3.7. The patients’ median age was 35 years (range 17-78), with 23 (43.4%) being female. The median time to response was 35 days (range 28-50 days) and the cumulative overall response rates (ORR) at day 30, day 60 and day 90 were 41.5%, 69.8%, and 81.1% respectively. A total of 10 patients on eltrombopag relapsed during follow up. The cumulative rate of relapse at one year, three years, and five years were 6.6%, 25.3%, and 47.7%, respectively. There was no significant difference in outcome (response rate or relapse) in any subgroups depending on age, sex, duration of disease, number of prior lines of treatment, splenectomy, or baseline platelet count. Six patients stopped eltrombopag after having a median sustained response for 796 days (range 658-1185), and after a median follow up of 624 days (range 92-1339), they continued to be in remission. Seventeen patients (17/53, 32%) reported one or more adverse events while on eltrombopag therapy. A total of 49 adverse events (n=4, grade ≥3 CTCAEv4) were noted. Anemia was the most frequent adverse event followed by hepatobiliary dysfunction as reflected by deranged AST/ALT or raised bilirubin. The use of eltrombopag among adult ITP patients in resource-constraint settings was well-tolerated and yielded excellent overall response. The benefit was found to be sustained on long-term follow up. However, events like anemia, hepatobiliary, and thrombotic complications merit closer follow up.